Differential Subcellular Localization and Expression of ATP Sulfurylase and 5′-Adenylylsulfate Reductase during Ontogenesis of Arabidopsis Leaves Indicates That Cytosolic and Plastid Forms of ATP Sulfurylase May Have Specialized Functions - Rotte, Carmen (American Society of Plant Physiologists, 2000)
ATP sulfurylase and 5′-adenylylsulfate (APS) reductase catalyze two reactions in the sulfate assimilation pathway. Cell fractionation of Arabidopsis leaves revealed that ATP sulfurylase isoenzymes exist in the chloroplast and the cytosol, whereas APS reductase is localized exclusively in chloroplasts. During development of Arabidopsis plants the total activity of ATP sulfurylase and APS reductase declines by 3-fold in leaves. The decline in APS reductase can be attributed to a reduction of enzyme during aging of individual leaves, the highest activity occurring in the youngest leaves and the lowest in fully expanded leaves. By contrast, total ATP sulfurylase activity declines proportionally in all the leaves. The distinct behavior of ATP sulfurylase can be attributed to reciprocal expression of the chloroplast and cytosolic isoenzymes. The chloroplast form, representing the more abundant isoenzyme, declines in parallel with APS reductase during aging; however, the cytosolic form increases over the same period. In total, the results suggest that cytosolic ATP sulfurylase plays a specialized function that is probably unrelated to sulfate reduction. A plausible function could be in generating APS for sulfation reactions.